THE PSYCHOSOCIAL FUNCTIONING OF WOMEN AND MEN ADDICTED TO ALCOHOL - Zajęcka, Beata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents how women and men addicted to alcohol function in basic areas of social life as well as what their psychical condition generally is. The conclusions are based on the theoretical findings and quality surveys. The research shows the equality does not exist in alcoholism. The men, contrary to the women: become addicted quicker, drink more alcohol, suffer from more somatic complications, more serious social damages arise especially conflicts with the law. What is more, they die more often due to alcohol intoxication. However, socio-cultural conditions show the women are more stigmatized than the men, what results in receiving non-effective support. The features about being an alcoholic are variant in reference to sex, particularly the development of an addiction as well as experiencing the alcoholism and the alcoholism addiction treatment. The revealed differences between sexes should allow improvement in already existing therapeutic solutions, notably to adjust them more individually. It will improve the quality of life in sobriety, people who are addicted to alcohol.